Tinjauan Ushul Fiqh terhadap Sumber Hukum Islam yang Diperselisihkan - Ramadhani, Syafa Al Zahra; Nugraha, Aszahra Regita; Millatillah, Mu’izzatu; Rahmawati, Irma Widya; Wafiuddin, Moch. Danish; Almadani, M. Zaqi; Kurniawan, Taufiq (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
In the study of ushul fiqh, Islamic legal sources occupy a fundamental position as a methodological framework in the process of establishing law. In addition to legal sources that have been widely agreed upon, such as the Al-Qur'an, Sunnah, ijma', and qiyas, there are also a number of other legal sources whose legal status is still debated among ulama. These differences arise due to variations in approaches to understanding propositions, the use of reason, and responses to social dynamics. This article comprehensively discusses disputed sources of Islamic law, including istihsan, maslahah murlah, 'urf, istishab, syar'u man qablana, sahabi school of thought, and sadd az-zari'ah, by highlighting the meaning, basis of argumentation, and its position in the ushul fiqh methodology. This research aims to expand understanding of the function of these legal sources as a means of ijtihad in resolving legal issues that are not explained directly in the Al-Qur'an and Sunnah. The method used is library research with a qualitative-descriptive approach through a review of classical and modern ushul fiqh literature. The analysis was carried out descriptively-analytically to describe the various views of ulama and the limits of application of each legal source. The results of the study show that even though the disputed legal sources are not accepted uniformly by all schools of thought, their existence still has an important role in the development of adaptive and contextual Islamic law. As long as their use does not conflict with the qath'i propositions and remains based on maqashid al-syariah, these legal sources are able to enrich the practice of ijtihad and maintain the relevance of Islamic law in the face of changing times.